Mammalian Cell-Based Immunoassay for Detection of Viable Bacterial Pathogens - Xu, Luping; Bai, Xingjian; Tenguria, Shivendra; Liu, Yi; Drolia, Rishi; Bhunia, Arun K. (Frontiers in Microbiology, 2020)
Rapid detection of live pathogens is of paramount importance to ensure food safety. At present, nucleic acid-based polymerase chain reaction and antibody-based lateral flow assays are the primary methods of choice for rapid detection, but these are prone to interference from inhibitors, and resident microbes. Moreover, the positive results may neither assure virulence potential nor viability of the analyte. In contrast, the mammalian cell-based assay detects pathogen interaction with the host cells and is responsive to only live pathogens, but the short shelf-life of the mammalian cells is the major impediment for its widespread application. An innovative approach to prolong the shelf-life of mammalian cells by using formalin was undertaken. Formalin (4% formaldehyde)-fixed human ileocecal adenocarcinoma cell line, HCT-8 on 24-well tissue culture plates was used for the capture of viable pathogens while an antibody was used for specific detection. The specificity of the Mammalian Cell-based ImmunoAssay (MaCIA) was validated with Salmonella enterica serovar Enteritidis and Typhimurium as model pathogens and further confirmed against a panel of 15 S. Enteritidis strains, 8 S. Typhimurium,11 other Salmonella serovars, and 14 non-Salmonella spp. The total detection time (sample-to-result) of MaCIA with artificially inoculated ground chicken, eggs, milk, and cake mix at 1-10 CFU/25 g was 16-21 h using a traditional enrichment set up but the detection time was shortened to 10-12 h using direct on-cell (MaCIA) enrichment. Formalin-fixed stable cell monolayers in MaCIA provide longer shelf-life (at least 14 weeks) for possible point-of-need deployment and multi-sample testing on a single plate.